Understanding hospitality service aesthetics through the lens of aesthetic theory. Issue 3 (3rd April 2023) - Wong, Ipkin Anthony; Wan, Yim King Penny; Sun, Danni
ABSTRACT: The pursuit of beauty has been a part of our daily lives, as the hospitality industry recognizes by offering aesthetically pleasing artifacts through a constellation of service attributes. This research takes a qualitative approach to explore hospitality service elements that are aesthetically appealing to customers. It draws on Adorno's aesthetic theory to better understand service aesthetics through the lens of the autonomous, socially determined, critical, and mimetic character of beauty. We improvise the concept of hospitality service aesthetic to notion that beauty is socially mediated in hospitality settings along five major themes: ocular-servicescape, facility spectacle, thematic embellishment, architectonic magnificence, and humanistic appearance. This inquiry also moves beyond the servicescape typology and prior empirical studies of aesthetics to acknowledge the constellation of environmental stimuli that can arouse customers from functional, emotional, symbolic, and socio-cultural perspectives.追求美已经成为我们日常生活的一部分, 正如酒店业通过一系列服务属性提供令人愉悦的艺术品所认识到的那样. 本研究采用定性方法来探索对顾客具有审美吸引力的酒店服务要素. 它借鉴了阿多诺的美学理论, 通过美的自主性、社会决定性、批判性和模仿性来更好地理解服务美学. 我们即兴提出了酒店服务美学的概念, 认为在酒店环境中, 美是通过五大主题进行社会调节的: 视觉服务景观、设施奇观、主题装饰、建筑华丽和人文外观. 这项调查也超越了服务景观类型学和先前的美学实证研究, 以确认可以从功能、情感、象征和社会文化角度激发顾客的环境刺激